Formation of the upper reaches of the Yellow River: Provenance evidence from the strata of the Yellow River sedimentary basin - Li, Baofeng; Feng, Qi; Wang, Xin; Li, Zaijun; Wang, Fei; Zhao, Chenguang; Yu, Tengfei; Chen, Weiyu (Global and planetary change, 2023)
The age of the formation of the upper reaches of the Yellow River is controversial, ranging from the Pliocene to the Middle Pleistocene. However, determining the source of the detrital materials within the Yellow River sedimentary basins outside the Tibetan Plateau can provide important evidence for resolving this issue. We conducted geochemical and heavy mineral studies of the sediments from a 274.60-m-long drill core from the Hetao Basin, the largest sedimentary basin in the upper reaches of the Yellow River. Our results suggest that detritus from the northeastern margin of Tibetan Plateau dominated the sedimentation within the Hetao Basin since ~1.68 Ma, with an average contribution of 68%. This suggests that the Yellow River that connected the northeastern margin of the Tibetan Plateau and the Hetao Basin was formed by at least the Early Pleistocene. Detritus from the distal Gobi-Altay Mts. and from the proximal Ordos Plateau and the Yin Mts. had average contributions of 28% and 4%, respectively. We conclude that the variations in the relative contributions of these three sources were related not only to the tectonic uplift of the Tibetan Plateau that driving integration of the Yellow River drainage system but also to the evolution of the East Asian monsoon system, as well as to global climate change. [Display omitted] •NE margin of Tibetan Plateau controlled Hetao Basin sedimentation since ~1.68 Ma•Yellow River connected Tibetan Plateau and Hetao Basin in the Early Pleistocene•Enhanced monsoon led to more debris from distal aeolian and proximal sources